2003
DOI: 10.1177/0739456x03258949
|View full text |Cite
|
Sign up to set email alerts
|

Do Distance Learning Efforts in Urban Planning Education Cut Short the Educational Experience?

Abstract: The application of distance learning to urban planning holds promise for reaching a broader planning education audience. While technology can bridge the gap between the classroomand the remote learner, the distance learner may be denied the opportunity of face-to-face communication, collaboration and inter-action when the traditional classroom experience is abandoned. This may not be in the best interest of students nor the clients assisted in the planning process. This article investigates the concern that te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Educators in planning (Lawhon 2003) and related fields such as geography (Dibiase 2000) express reservations about the effectiveness of e-learning, but at the same time the benefits for enriching the quality of learning resources and expanding the reach of education needs to be weighted into the argument. Accepting that elearning is inevitable, it is important to review the way course design and facilitated learning takes place (Lawhon 2003).…”
Section: Brief Synopsis Of E-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Educators in planning (Lawhon 2003) and related fields such as geography (Dibiase 2000) express reservations about the effectiveness of e-learning, but at the same time the benefits for enriching the quality of learning resources and expanding the reach of education needs to be weighted into the argument. Accepting that elearning is inevitable, it is important to review the way course design and facilitated learning takes place (Lawhon 2003).…”
Section: Brief Synopsis Of E-learningmentioning
confidence: 99%
“…Accepting that elearning is inevitable, it is important to review the way course design and facilitated learning takes place (Lawhon 2003). E-learning has changed the way learning occurs with a shift toward constructive learning, in which learners are given the opportunity to construct their own meaning from the information presented during the online sessions (Lebow 1993;Ally 2004).…”
Section: Brief Synopsis Of E-learningmentioning
confidence: 99%
“…Deadman et al (2000) as well as Lawhon (2003) indicated that online courses can never be a substitute for classroom instruction. Rather, self-learning modules should be designed to complement, rather than replace, the existing traditional approaches of the classroom (Zerger et al, 2002).…”
Section: Methods Of Instruction For Gis Integrated Planning Coursesmentioning
confidence: 96%
“…Educators have also raised questions concerning the effectiveness of technologyenhanced online courses, particularly if it cuts short essential student experiences (Ali & Doan, 2006;Lawhon, 2003). Deadman et al (2000) as well as Lawhon (2003) indicated that online courses can never be a substitute for classroom instruction.…”
Section: Methods Of Instruction For Gis Integrated Planning Coursesmentioning
confidence: 98%
See 1 more Smart Citation